0 like 0 dislike
Question 8 of 10
If f(x) = 3x - 2 and g(x) = 2x + 1, find (f- g)(x).
OA. x-3
B. 5x - 1
OC. 5x-3
OD. 3-x
SUB
by

2 Answers

0 like 0 dislike
a) x - 3

Step-by-step explanation:

Given:

a) (f)(x) = 3x - 2

b) (g)(x) = 2x + 1

Find (f - g)(x):

(f - g)(x) = f(x) - g(x)

(f - g)(x) = (3x - 2) - (2x + 1) [subtract]

(f - g)(x) = 3x - 2x - 2 - 1 [combine like terms]

(f - g)(x) = x - 3

Learn more about subtracting functions here:

27846660

16287318
by
0 like 0 dislike
A

Step-by-step explanation:

when adding or subtracting (or multiplying or dividing) functions, we do this by applying the same operation to the functional expressions.

(f-g)(x) = (3x - 2) - (2x + 1) = 3x - 2 - 2x - 1 = x - 3

so, A is the correct answer.
by
Welcome to AskTheTask.com, where understudies, educators and math devotees can ask and respond to any number related inquiry. Find support and replies to any numerical statement including variable based math, geometry, calculation, analytics, geometry, divisions, settling articulation, improving on articulations from there, the sky is the limit. Find solutions to numerical problems. Help is consistently 100 percent free!

Questions

No related questions found